2022
DOI: 10.1155/2022/8392313
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicle-Derived circITGB1 Regulates Dendritic Cell Maturation and Cardiac Inflammation via miR-342-3p/NFAM1

Abstract: Acute myocardial infarction (AMI) is a complication of atherosclerosis-related cardiovascular illness that is caused by prolonged ischemia. Circular RNAs (circRNAs) are concentrated in extracellular vesicles (EVs) and have been linked to cardiovascular disease. However, additional research is needed into the expression and function of circRNAs in AMI. In this study, circITGB1 (has_circRNA_0018146), derived from exon 1 of the ITGB1 gene localized on chromosome 10, was shown to be considerably increased in plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Second, long-term exercise-derived exosomal miR-342-5p not only targets the Caspase-9 and JNK2 pathways but also enhances survival signaling (p-Akt) by targeting the phosphatase gene Ppm1f to protect the heart from MI/R injury (Hou et al, 2019). From the same gene family, miR-342-3p has also been proven to participate in the regulatory processes related to acute myocardial infarction (AMI) by increasing the expression of NFAT activating molecule 1 (NFAM1) to combat myocardial injury (Zhu et al, 2022). Third, the expression of exercise-derived EV proteins ALIX and RAB35 activates ERK1/2 and HSP27 signals to protect against cardiac I/R injury (Bei et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Second, long-term exercise-derived exosomal miR-342-5p not only targets the Caspase-9 and JNK2 pathways but also enhances survival signaling (p-Akt) by targeting the phosphatase gene Ppm1f to protect the heart from MI/R injury (Hou et al, 2019). From the same gene family, miR-342-3p has also been proven to participate in the regulatory processes related to acute myocardial infarction (AMI) by increasing the expression of NFAT activating molecule 1 (NFAM1) to combat myocardial injury (Zhu et al, 2022). Third, the expression of exercise-derived EV proteins ALIX and RAB35 activates ERK1/2 and HSP27 signals to protect against cardiac I/R injury (Bei et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Another circRNA that also increases its expression in exosomes after MI is circITGB1. Within in vivo assays using a mouse model, these exosomes activate dendritic cells and exacerbate cardiac damage and inflammation through the miR-342-3p/NFAM1 pathway [86]. In vitro assays have also been reported in CMs subjected to hypoxia where high levels of circ_HIPK3 and circ_SLC8A1 are detected [87,88].…”
Section: Small Extracellular Vesicle Transcriptomic Analyses In Myoca...mentioning
confidence: 97%
“…Several circRNAs are upregulated in AMI patients, such as circITGB1 and circ_0023461, while studies have shown that circHelz and circ_0007059 are elevated in MI in mice [ 81 , 237 , 238 , 239 ]. Additionally, numerous other circRNAs are upregulated in experimental hypoxia models in vitro, such as circ_0023461, circHelz, circ_0007059, circ_0001747, circTRRAP, and circMAT2B [ 80 , 81 , 238 , 239 , 242 ].…”
Section: Circrnas In Cardiac Infarction and Regenerationmentioning
confidence: 99%
“…circITGB1 controls dendritic cell maturation by targeting miR-342-3p and NFAM1. circITGB1 also exacerbated cardiac damage and regulated miR-342-3p and NFAM1 expression in a mouse AMI model [ 237 ]. Similarly, circ_0023461 expression is upregulated in AMI patients and hypoxia-induced AC16 cells, and it can upregulate PDE4D expression by acting as a molecular sponge for miR-370-3p in AC16 cells [ 238 ].…”
Section: Circrnas In Cardiac Infarction and Regenerationmentioning
confidence: 99%